Gene expression in the embryonic nervous system of Xenopus laevis. - Klaus Richter; Horst Grunz; Igor B. Dawid (1988)
Development of the nervous system in the amphibian embryo is initiated during gastrulation by an inductive interaction between chordamesoderm and dorsal ectoderm. The induced ectoderm forms the neural plate while uninduced ectoderm generates epidermis. We screened for genes activated during gastrulation and expressed specifically in the nervous system of Xenopus laevis in the expectation that clones representing such genes will constitute useful markers for the study of early neurogenesis. Probes were prepared from adult brain RNA by subtraction with RNA from ovary and from different combinations of adult kidney, muscle, and skin; cDNA libraries prepared from early to late neurula embryo RNA were screened with these probes. Six clones were chosen for further study. Three of these clones are not represented in the maternal RNA population but are activated at the late gastrula stage; the other three increase from a maternal base. Expression of five of the genes is restricted to the neural plate during embryogenesis, and all six are restricted to the central nervous system in premetamorphic tadpoles and adults. One of the clones encodes an apparently neurospecific isoform of beta-tubulin; the identity of the other clones is unknown. Expression of all six genes is suppressed in axis-deficient embryos that lack dorsal structures including the brain.